Adenovirus terminal protein protects single stranded DNA from digestion by a cellular exonuclease. - Dunsworth-Browne, M (1980)
Adenovirus 5 DNA-protein complex is isolated from virions as a duplex DNA molecule covalently attached by the 5' termini of each strand to virion protein of unknown function. The DNA-protein complex can be digested with E. coli exonuclease III to generate molecules analogous to DNA replication intermediates in that they contain long single stranded regions ending in 5' termini bound to terminal protein. The infectivity of pronase digested Adenovirus 5 DNA is greatly diminished by exonuclease III digestion. However, the infectivity of the DNA-protein complex is not significantly altered when up to at least 2400 nucleotides are removed from the 3' ends of each strand. This indicates that the terminal protein protects 5' terminated single stranded regions from digestion by a cellular exonuclease. DNA-protein complex prepared from a host range mutant with a mutation mapping in the left 4% of the genome was digested with exonuclease III, hybridized to a wild type restriction fragment comprising the left 8% of the genome, and transfected into HeLa cells. Virus with wild type phenotype was recovered at high frequency.